A self-powered and reagent-less electrochemical aptasensor based on a DNA walker and tetraferrocene for the detection of aflatoxin B1. Issue 37 (8th September 2022) - Fan, Hao; Cheng, Mengqing; Zhang, Wenxing; Hong, Nian; Wei, Guobing; Huang, Ting; Cui, Hanfeng; Zhang, Jing
Abstract : The constructed DNA walker is highly integrated in the form of Mn 2+ @UIO-66(Zr)–(COOH)2 without additional metal ions. Tetraferrocene was synthesized to enhance the sensitivity of E-AB sensors. We developed a sensor that is sensitive, with a detection limit of 4.8 fg mL −1 . Abstract : We constructed a self-powered and reagent-less electrochemical aptamer sensor for sensitive detection of aflatoxin B1 (AFB1). Here, the metal ion Mn 2+ required for the DNAzyme to drive a DNA walker is wrapped in UIO-66(Zr)–(COOH)2 and AFB1 triggers the DNAzyme walking strands to automatically and continuously cut the tetraferrocene-labeled substrate strands, which results in a significant decrease in the electrochemical signal. Under the optimal conditions, the concentration dependence of AFB1 is linear in the concentration range of 0.1 pg mL −1 to 0.195 μg mL −1, and the limit of detection is as low as 4.8 fg mL −1 . The sensor displayed good performance even for samples with a complex matrix, such as a peanut sample. The recoveries of AFB1 obtained ranged from 95.5 to 106.8%. The developed sensing platform is reagent-less, self-powered, and highly sensitive. It holds great potential for detection of AFB1 in environmental and food samples.